Nonuniqueness Solution Forms of Close-Coupling Equations for e-He Scattering - Agus Kartono; Toto Winata (Institut Teknologi Bandung, 2003)
The close-coupling method relies on the reformulation of the SchrÃ¶dinger equation into an infinite set of coupledchannel equations by expanding over the complete set of target states. The target states approach will be used is a restricted basis for helium states in which one of the electrons is in a fixed orbital (1s) while the second electron is described by a set of independent L2 functions, thus permitting it to span the discrete and continuum excitations. This type of approximate description of the target should be good for scattering problems in which the dominant reaction mechanism is by one-particle (electron) excitations. We will also show why the standard close-coupling expansion gives rise to nonunique solutions.